Wine production in the phoenician and punic world. Notes about wine culture and consumption through the archaeological and literary sources - Prados Martínez, Fernando (Gerión. Revista de Historia Antigua, 2012)
In this article we will make an analysis on the knowledge of vineyard in the world of Carthage and the production and export of Phoenician and Punic wine through the archaeological and literary sources. We must rely, therefore, references to classic texts (Mago, Virgilio Columela) and data from archaeological excavations in Carthage and its environment. In addition, to complement the information, we will also study the presence of grape seeds –Vitis vinifera– into the botanical analysis of some archaeological places.
Keywords: Phoenicians; punics; wine; vineyard; production and trade.